Evaluation Of Lipid Profile, and Preptin Between Obese Non-Diabetic Patients and Women with Polycystic Ovary Syndrome in Al Diwaniyah, Iraq - Alobaidy, Zainab; Alammar, Haider; AL-harmooshee, Maather (Journal of Biomedicine and Biochemistry, 2023)
Background Obesity has been associated with polycystic ovarian syn- drome (PCOS) since Stein and Leventhal first described it in 1935. When using equivalent diagnostic criteria. This implies that lifestyle variables like obesity cause PCOS. Obesity worsens PCOS-related reproductive and metabolic problems.Materials and Method The present study included 40 women with polycystic ovarian syndrome at ages (17 -36) years, in addition, the study included 40 non-diabetic obese women with a mean age range of (18 -56) years, Between November 2022 and May 2023, the participants in this research were enrolled at Al-Diwanyah Teaching Hospital. All laboratory test analysis was completed at the Clinical Chemistry Research Lab and AL Diwaniyah Teaching Hospital, both located in the College of Medicine at the University of Al-Qadisiyah.Results In the present results lipid profile, the mean cholesterol was significantly higher in the PCOS Group in comparison with the obese OND . There was no significant difference in the mean serum triglycerides, HDL, LDL, and VLDL between the PCOS Group and the OND group. There was no significant difference in the mean preptin level between the PCOS group and the obese OND (p = 0.473). Then there was a comparison of preptin levels before and after the treatment in OND patients there was a significant reduction in the level (p < 0.001), and in comparison of preptin levels before and after the treatment in PCOS patients there was a significant reduction in the level (p < 0.001).Conclusion According to the current findings, treating overweight or obese PCOS patients with insulin resistance, the Homeostatic Model As- sessment for Insulin Resistance, and metformin had comparable outcomes.